Differential geometry of submanifolds and its related topics proceedings of the International Workshop in honor of S. Maeda's 60th birthday : Saga University, Saga, Japan, 4-6 August 2012 - Maeda, Sadahiro; Ohnita, Yoshihiro, 1958-; Cheng, Qing-Ming (World Scientific, 2014)
This volume is a compilation of papers presented at the conference on differential geometry, in particular, minimal surfaces, real hypersurfaces of a non-flat complex space form, submanifolds of symmetric spaces and curve theory. It also contains new results or brief surveys in these areas. This volume provides fundamental knowledge to readers (such as differential geometers) who are interested in the theory of real hypersurfaces in a non-flat complex space form --